СОВЕТСКИЕ ЖУРНАЛЬНЫЕ ДИСКУССИИ КОНЦА 60-Х И НАЧАЛА 70-Х ГГ. ХХ В. КАК ПРИЗНАК ВРЕМЕНИ - Pospíšil, Ivo (Przegląd Rusycystyczny, 2016)
THE SOV IET JOURN AL DISCUSS IONS AT THE END OF THE 1960s AND AT THE BEG INN ING OF THE 1970s AS A SY MPTO M OF THEIR TIME S u m m a r y The author of the present study tries to analyse the structure and character of the two discussions (on Russian Slavophiles and revolutionary democtrats) which proceeded on the pages of the journal “Voprosy literatury” (Problems of Literature) at the end of the 1960s and at the beginning of the 1970s. In the study the author demonstrates the shifts towards the twofold shape of Russian thought, towards philosophical idealism and the contact with the current development of the Soviet so-called “village literature”. Though this tendency seemed to be rather hidden, concealed, it could not take place without the consent of political authorities which manifested the ideological searching even in these ruling circles of that time.